Efektivitas Ombudsman RI Perwakilan Provinsi Jawa Tengah Dalam Melaksanakan Fungsi Monitoring Penyelenggaraan Ujian Nasional Berbasis Komputer Tingkat SMA/SMK/MA Di Jawa Tengah - Putri Dwi Andana; Warsito . (Journal of Politic and Government Studies, 2017)
ABSTRACTIONThis research is focussed on knowing, studying, and analyzing about The Effectiveness of Ombudsman RI Representative Central Java in Implementing The Monitoring Function of the Computer-Based National Test of SMA/SMK/MA in Central Java. In other hand, it will see the factors which influences The Effectiveness of Ombudsman RI Representative Central Java doing its function.The experimental method used descriptive qualitative. The data sources from the primary data through in deep interview with key person. Meanwhile, secondary data sources from documentary, achieve approach has been used in this research aimed for understanding key person response to the supporting expression on the real fact. Then it can be disscussed and make a conclusion based on the result of research by writting, words or sentences.The Effectiveness of Ombudsman RI Representative Central Java is important thing to measure in case this department will be useful and whatever the task and function is appropriate. The result of this research shows that Ombudsman RI Representative Central Java hasn’t effective yet because the purpose the monitoring hasn’t achieved. Ombudsman RI Representative Central Java can’t make sure the held of the Computer-Based National Test of SMA/SMK/MA in Central Java running well, orderly and accountable as well as written in the news letter of Ombudsman RI Representative Central Java. Mean while the main factors that influence The Effectiveness of Ombudsman RI Representative Central Java is human resourcess and facilities they have.Keywords: Effectiveness, Monitoring, UNBK Policy, Ombudsman RI Representative Central Java.